FAMILY DAKWAH - Shubhan Hafidz (Fakultas Agama Islam, Universitas Islam As-Syafiiyah, 2021)
Family Da'wah is a concept of da'wah which is being the foundation and guide in building an Islamic family. This concept actually aspires to form individuals as